Genetic variant rs4072037 of MUC1 and gastric cancer risk in an Eastern Chinese population - Qiu, Li-Xin (Oncotarget, 2016)
Published data on the association between the MUC1 rs4072037A > G polymorphism and gastric cancer (GCa) risk were inconclusive. To derive a more precise estimation of the association, we conducted a large GCa study of 1,124 cases and 1,192 controls to confirm this association in an Eastern Chinese population. Our results showed that the G allele was strongly associated with a decreased GCa risk in the study population [GG vs. AA, odds ratio (OR) = 0.47, 95% confidence interval (CI) = 0.31–0.73; AG/GG vs. AA, OR = 0.82, 95% CI = 0.68–0.99; GG vs. AA/AG, OR = 0.48, 95% CI = 0.32–0.74]. These associations remained significant in subgroups of age, tumor site, drinking and smoking status. Moreover, this association was supported by an additional meta-analysis of published studies. In summary, these results suggest that the MUC1 rs4072037G allele may be a low-penetrating protection factor for GCa risk in Chinese populations.